Methane Decomposition Over ZrO2-Supported Fe and Fe–Ni Catalysts—Effects of Doping La2O3 and WO3 - Fakeeha, Anis H.; Kasim, Samsudeen Olajide; Ibrahim, Ahmed Aidid; Al-Awadi, Abdulrhman S.; Alzahrani, Eman; Abasaeed, Ahmed Elhag; Awadallah, Ahmed E.; Al-Fatesh, Ahmed Sadeq (Frontiers in Chemistry, 2020)
A leading method for hydrogen production that is free of carbon oxides is catalytic methane decomposition. In this research, Fe and Fe-Ni supported catalysts prepared by wet impregnation method were used in the methane decomposition. The effects of doping the parent support (ZrO2) with La2O3 and WO3 were studied. It was discovered that the support doped with La2O3 gave the best performance in terms of CH4 conversion, H2 yield and stability at the test condition, 800 °C and 4,000 ml/h/g-cat space velocity. Addition of Ni significantly improved the performance of all the monometallic catalysts. The catalysts were characterized by the XRD, BET, TPR/TPO, TGA and microscopy (SEM, Raman) techniques. Phases of different forms of Fe were identified by the XRD, BET showed a drastic decline in the specific surface area of the catalysts with respect to the supports. TPR profiles revealed a progressive change in the valency of Fe in its combined form to the zero valence free metal. The La2O3 promoted support gave the best performance and maintained good stability during the time on stream.